2018
DOI: 10.1002/adma.201802397
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Polymorphs in Molybdenum Disulfide via Electron Microscopy

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201802397. The presence of rich polymorphs and stacking polytypes in molybdenum disulfide (MoS 2 ) endows it with a diverse range of electrical, catalytic, optical, and magnetic properties. This has stimulated a lot of interest in the unique properties associated with each polymorph. Most techniques used for polymorph identification in MoS 2 are macroscopic techniques that sample averaged proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 80 publications
1
102
0
Order By: Relevance
“…As we know, the contrast of STEM image is dependent on the atomic number Z ( I ∝ Z 1.6−1.7 ), which can be employed to differentiate atomic species (Figure 3f). [ 33,34 ] Moreover, the uniform distribution of bright and gray spots demonstrates the absence of defects, indicating the high crystalline quality. All in all, the above TEM and STEM results demonstrate that VS 2 exhibits the hexagonal phase with high crystalline quality.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the contrast of STEM image is dependent on the atomic number Z ( I ∝ Z 1.6−1.7 ), which can be employed to differentiate atomic species (Figure 3f). [ 33,34 ] Moreover, the uniform distribution of bright and gray spots demonstrates the absence of defects, indicating the high crystalline quality. All in all, the above TEM and STEM results demonstrate that VS 2 exhibits the hexagonal phase with high crystalline quality.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we applied STEM‐ADF imaging to investigate the crystallinity of the BiOCl crystals. The contrast of STEM‐ADF image is dependent on the Z atomic number as approximately ∼Z 1.6‐1.7 , thereby it was widely employed for analyzing crystal structures and atomic defects in 2D materials . From the theoretical atomic model (Figure A), we can see that BiOCl crystal shows a perfect tetragonal lattice along the [001] zone axis.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been found that hydrothermal synthesis of MoS 2 doped with Re induces 2H-1T phase transformation [18], we cannot specifically identify this phase transformation in our results due to special features of MoS 2 synthesized under solvothermal conditions. These include easy oxidation of samples in environmental conditions during Raman acquisition ( Figure S5) [31]; difficulty in identifying the 1T/2H phase of few-layered MoS 2 materials in TEM [37]; and existence of molybdenum polysulfides (considering solvothermal synthesis conditions) for XPS [38]. Our electrocatalytic results show that low Re doping improves overall HER catalytic activity of MoS 2 due to the creation of new catalytically active sites in basal planes, and by decreasing charge transfer resistance in the doped material.…”
Section: Hydrogen Evolution Reaction (Her) Performance Of Pristine Momentioning
confidence: 99%